Determining requirements and challenges for a sustainable and circular electric vehicle battery supply chain: A mixed-methods approach - Gebhardt, Maximilian; Beck, Janina; Kopyto, Matthias; Spieske, Alexander (Sustainable Production and Consumption, 2022)
Limited transparency on the sustainability of the lithium-ion battery supply chain (LIBSC) could impede a rapid scale-up of the electric vehicle battery ecosystem, which is required for the decarbonization of the transportation sector. A comprehensive and commonly accepted framework to assess the sustainability of this industry is currently missing. To address this research gap, a mixed-methods approach comprising a literature review, several expert interviews, two workshops, and a two-round Delphi study is conducted. 29 aspects concerning the LIBSC's sustainability are derived and prioritized according to their importance and ease of implementation. Furthermore, 30 barriers for establishing the required transparency in the LIBSC are identified. The results show that a broad range of criteria has to be incorporated to comprehensively evaluate battery sustainability. Thereby, greenhouse gas emissions, circularity indicators, and human rights and safety issues are considered the most crucial, while the least importance is attributed to economic aspects. A broad range of barriers to such assessments are identified, many of which stem from the interaction and relationships among supply chain tiers or originate at one tier and affect another upstream or downstream counterpart. Overall, the study's results indicate that assuring compliance with existing sustainability standards might be a feasible and pragmatic approach to cope with the considerable variety of important sustainability aspects. Moreover, the identified barriers imply that meaningful assessments can only be achieved via cross-tier assessments and considerable collaborations among the stakeholders of the rapidly evolving LIBSC.
CRIS-Team Scopus Importer:2022-07-22
Keywords: Circular economy; Delphi study; Electric vehicles; Lithium-ion battery; Mixed-methods; Sustainability assessment

How did supply chain networks handle the COVID-19 pandemic? Empirical evidence from an automotive case study - Spieske, Alexander; Gebhardt, Maximilian; Kopyto, Matthias; Birkel, Hendrik; Hartmann, Evi (International Journal of Physical Distribution & Logistics Management, 2022)
Purpose: The coronavirus disease 2019 (COVID-19) pandemic unveiled resilience deficits in supply chains. Scholars and practitioners aim to identify supply chain resilience (SCRES) measures suitable for this unique disruption; however, empirical evidence on a pandemic's specific characteristics, resulting challenges, and suitable countermeasures is scarce. Design/methodology/approach: A single-case study on an automotive supply chain network (ASCN), including eight nodes, was conducted. Based on current research and interviews with 35 experts, characteristic pandemic challenges for the ASCN were identified. Moreover, promising SCRES measures were determined along the most prominent SCRES levers. The findings lead to five central propositions and advance organizational information processing theory in the context of SCRES. Findings: This study’s results confirm unique pandemic characteristics along the supply chain disruption's duration, severity, propagation, and volatility. The resulting unprecedented challenges made the ASCN apply novel SCRES measures, particularly regarding collaboration and risk management culture. However, well-known visibility and flexibility strategies were also suitable. Overall, agility and collaboration measures showed the highest capacity to address characteristic pandemic challenges. A lack of preparedness impeded some measures' application, calling for enhanced proactive risk management following the pandemic. Originality/value: This paper addresses several research calls by providing in-depth empirical evidence on hitherto conceptually researched pandemic characteristics, challenges, and suitable SCRES measures from a network perspective. The study uncovers the different perceptions of individual tiers, emphasizing the need to analyze supply chain disruptions from multiple angles.
CRIS-Team Scopus Importer:2022-06-17
Keywords: Automotive supply chain; Case study; COVID-19 pandemic; Organizational information processing theory; Supply chain network; Supply chain resilience

Improving resilience of the healthcare supply chain in a pandemic: Evidence from Europe during the COVID-19 crisis - Spieske, Alexander; Gebhardt, Maximilian; Kopyto, Matthias; Birkel, Hendrik (Journal of Purchasing and Supply Management, 2022)
The severe scarcity of critical medical supplies caused by the COVID-19 pandemic led to considerable procurement challenges in the healthcare supply chain (HCSC). As ensuring the availability of such supplies during disruptions is critical, the debate on how to increase supply chain resilience in healthcare has gained new momentum. We present empirical evidence from a multi-tier case study spanning nine European medical supplies manufacturers and hospital groups. Based on the resource dependence theory, we investigated procurement-related strategies to improve medical supplies availability. We conducted semi-structured interviews with 39 procurement and supply chain management experts and derived seven propositions on buffering and bridging approaches for managing evolving resource dependencies and thereby strengthening supply chain resilience in a pandemic. Overall, we confirm the resource dependence theory's applicability for explaining companies' mitigation measures in a pandemic disruption. We find that bridging measures within the healthcare supply base, such as offering procurement support for suppliers or leveraging long-term buyer-supplier relationships, are more effective for securing medical supplies than buffering measures. Complementing bridging with buffering, such as extended upstream procurement or resource sharing among hospitals, can lead to superior risk mitigation as capacities of the present supplier base may not suffice. Furthermore, we extend the resource dependence theory by showing that the severity of disruptions caused by a pandemic triggers new forms of buffering external to the HCSC. Both traditional and new buffering measures establish novel flows of medical supplies in the HCSC that can enable higher supply security in a pandemic.
CRIS-Team Scopus Importer:2022-12-09
Keywords: Case study; COVID-19 pandemic; Healthcare procurement; Healthcare supply chain; Resource dependence theory; Supply chain resilience

Increasing global supply chains’ resilience after the COVID-19 pandemic: Empirical results from a Delphi study - Gebhardt, Maximilian; Spieske, Alexander; Kopyto, Matthias; Birkel, Hendrik (Journal of Business Research, 2022)
COVID-19 has revealed global supply chains’ vulnerability and sparked debate about increasing supply chain resilience (SCRES). Previous SCRES research has primarily focused on near-term responses to large-scale disruptions, neglecting long-term resilience approaches. We address this research gap by presenting empirical evidence from a Delphi study. Based on the resource dependence theory, we developed 10 projections for 2025 on promising supply chain adaptations, which were assessed by 94 international supply chain experts from academia and industry. The results reveal that companies prioritize bridging over buffering approaches as long-term responses for increasing SCRES. Promising measures include increasing risk criteria importance in supplier selection, supply chain collaboration, and supply chain mapping. In contrast, experts ascribe less priority to safety stocks and coopetition. Moreover, we present a stakeholder analysis confirming one of the resource dependence theory’s central propositions for the future of global supply chains: companies differently affected by externalities will choose different countermeasures.<br
Keywords: COVID-19 pandemic; Delphi study; Supply chain disruption; Supply chain resilience; Supply chain risk management; Resource dependence theory

Increasing supply chain resilience after the COVID-19 pandemic: a resource dependence perspective - Spieske, Alexander; Gebhardt, Maximilian; Kopyto, Matthias; Birkel, Hendrik (Production and Operations Management Society (POMS), 2021)

Industry 4.0 and supply chain resilience - Gebhardt, Maximilian; Spieske, Alexander; Kopyto, Matthias; Birkel, Hendrik (Proceedings of the Annual International Purchasing & Supply Education & Research Association (IPSERA) Online Conference 2021, 2021)

Industry 4.0 technologies as enablers of collaboration in circular supply chains: a systematic literature review - Gebhardt, Maximilian; Kopyto, Matthias; Birkel, Hendrik; Hartmann, Evi (International Journal of Production Research, 2021)
Close and novel forms of collaboration among supply chain stakeholders within and beyond industry boundaries are essential for implementing a circular economy. Industry 4.0 technologies, as recognised enablers for circular systems, can support such collaboration. This study explores the intersection of the circular economy, supply chain collaboration, and Industry 4.0. First, we derive an analytical framework that contextualises circular supply chain collaboration. Second, based on this framework, we conduct a systematic literature review that explores how Industry 4.0 technologies can enable collaboration mechanisms. The review shows that information sharing and joint planning and decision-making are the most common collaboration mechanisms studied. Simultaneously, the Internet of Things, Blockchain, and Cloud Systems are the most discussed technologies to enable those mechanisms. The most prominent review sample patterns are synthesised into three archetypes for Industry 4.0-enabled circular supply chain collaboration. Furthermore, the study derives nine promising questions for future research along six main dimensions: Digital Twins and Artificial Intelligence, joint knowledge creation and innovation, collaboration in product design and planning, systemic collaboration across industry boundaries, contextualisation with barriers for implementing circular supply chains, and transferability of applications across industries.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Circular economy; collaboration; digital technology; industry 4.0; supply chain management

Resilience of the healthcare supply chain during the COVID-19 pandemic - Gebhardt, Maximilian; Spieske, Alexander; Kopyto, Matthias; Birkel, Hendrik (Production and Operations Management Society (POMS), 2021)

Supply Chain Resilience during the COVID-19 Pandemic: Learnings from a Multiple Case Study Design - Spieske, Alexander; Gebhardt, Maximilian; Kopyto, Matthias; Birkel, Hendrik (Proceedings of the Annual International Purchasing & Supply Education & Research Association (IPSERA) Online Conference 2021, 2021)
The COVID-19 pandemic revealed important gaps in companies’ risk management and scholars’ previous contributions to supply chain resilience literature. We present empirical evidence from a multiple case study design to identify specific supply chain challenges caused by a pandemic and potential mitigation measures. Based on a new supply chain resilience framework, we analyze companies’ challenges, countermeasures, and resilience objectives during the COVID-19 pandemic. Furthermore, we perform a cross-case analysis and develop insights on steering supply chains successfully through a pandemic. Our findings reveal that strengthening the existing supply base and leveraging digital technologies are promising mitigation measures in a pandemi

The future of industry 4.0 and supply chain resilience after the COVID-19 pandemic: Empirical evidence from a Delphi study - Spieske, Alexander; Gebhardt, Maximilian; Kopyto, Matthias; Birkel, Hendrik; Hartmann, Evi (Computers & Industrial Engineering, 2023)
The COVID-19 pandemic has caused major supply chain disruptions and unveiled the pressing need to improve supply chain resilience (SCRES). Industry 4.0 (I4.0) is a promising lever; however, its future in supply chain risk management (SCRM) is highly uncertain and largely unexplored. This paper aims to evaluate I4.0′s potential to improve SCRES in a post-COVID-19 world. Based on current literature and multiple workshops, 13 future projections on potential I4.0 application areas in SCRM were developed. A two-round Delphi study among 64 SCRM experts with digital expertise was conducted to evaluate and discuss the projections regarding their probability of occurrence until 2030, their impact on SCRES, and their desirability. A fuzzy c-means algorithm was applied to cluster the projections based on the expert assessments. The expert evaluations led to three clusters on I4.0 application in SCRM: Four projections on generating data, increasing visibility, and building digital capabilities received considerable approval and are reliable to improve SCRES in 2030. Four projections enabling data sharing and processing were predominantly supported and demonstrated realization potential for 2030. Finally, five projections that require major supply network adaptations were deemed unlikely to improve SCRES in 2030. This paper answers several research calls by presenting empirical evidence on the pathway of I4.0 implementation in SCRM following the COVID-19 pandemic. Moreover, it evaluates a holistic set of technologies and indicates prioritization potentials to achieve SCRES improvements.
CRIS-Team Scopus Importer:2023-06-09
Keywords: COVID-19 pandemic; Delphi study; Digital supply chain; Industry 4.0; Supply chain Resilience; Supply Chain Risk

The future of the circular economy and its effect on supply chain dependencies: Empirical evidence from a Delphi study - Gebhardt, Maximilian; Spieske, Alexander; Birkel, Hendrik (Transportation Research Part E-Logistics and Transportation Review, 2022)
This paper conducts a Delphi study to empirically explore the future roadmap of the circular economy (CE). Moreover, we build on the resource dependence theory to explore the CE’s potential to reduce dependencies in supply chain (SC) networks. Based on current literature, the CE practices of the 4R framework (reduce, reuse, recycle, recover), and a series of workshops, we formulated 11 future-oriented projections. In two subsequent Delphi rounds, 78 international CE and SC management experts quantitatively assessed the projections regarding their probability of occurrence in 2030, their potential to reduce SC dependencies, and their desirability. A fuzzy c-means algorithm was applied to cluster the projections based on the expert assessments. We found that the implementation likelihood of CE practices in 2030 is not congruent with the value retention hierarchy advocated by the 4R framework. Qualitative analyses of the panelists’ written statements revealed that regulation, financial attractiveness, customer demand, technological innovation, and product design are the most prominent influencing factors for the future implementation of various CE practices. Moreover, different practices revealed a varying capacity to reduce SC dependencies. More precisely, we found that diversifying a company’s supply base through recycled materials and components has the highest potential. Our qualitative data further provides evidence that CE practices’ capacity to lift dependencies can become an enabler for SC resilience.
Keywords: Circular economy; Sustainable supply chain management; Supply chain resilience; Delphi study; Resource dependence theory

Will the blockchain solve the supply chain resilience challenges? Insights from a systematic literature review - Beck, Janina; Birkel, Hendrik; Spieske, Alexander; Gebhardt, Maximilian (Computers & Industrial Engineering, 2023)
Frequency and severity of supply chain disruptions are increasing, and new solutions for improving supply chain resilience (SCRES) are demanded. Operations managers and scholars place great hopes on recent technological innovations, particularly blockchain technology. However, the current literature lacks a comprehensive review at the intersection of SCRES and blockchain, making it difficult to understand the relations between both fields holistically. This research gap was addressed by systematically analyzing 72 peer-reviewed papers. More specifically, the link between specific blockchain characteristics, SCRES antecedents, and supply chain risk types was explored. The results reveal that visibility and validation are the most relevant blockchain characteristics for improving SCRES. The SCRES antecedents agility, collaboration, and supply chain (re-)engineering can all benefit from blockchain implementation, whereas the effect on risk management culture is widely unexplored. While there is consensus on blockchain's usability for mitigating security, operational, and supply risks, the effect on demand risks requires further attention. To facilitate the practical implementation of this paper's results, the findings served as a foundation for discussing SCRES opportunities from well-known blockchain applications such as smart contracts and tracking solutions. Moreover, seven future research avenues and managerial implications are presented.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Blockchain; Distributed ledger; Literature review; Supply chain disruption; Supply chain resilience; Supply chain risk management